Integrasi E-Commerce dengan Sistem Ekonomi Syariah: Sebuah Kajian Teoritis - Kharisma Gusti Pelita; Rizky Ramadhania; Cantika Yuliandanil; Ahmad Hafiz Al faqih; Fadhil Ridho Akbar; Ilham Al-irsyad; Maulana Amar Fauzan (Journal of Economics and Business, 2024)
ABSTRACTE-commerce has become an integral part of the global economic system, facilitating trade transactions digitally. However, in the context of Islamic economics, there are principles that must be followed to ensure transactions are conducted in accordance with Islamic law. This article aims to examine the integration of e-commerce with the Islamic economic system, by identifying challenges, opportunities, as well as Islamic economic principles that are relevant in e-commerce practices. This research uses a qualitative approach with a literature study related to e-commerce and Islamic economics. The results show that although there are challenges in implementing sharia principles on digital platforms, there is great potential for sharia e-commerce to develop by prioritizing the principles of fairness, transparency, and the prohibition of usury.ABSTRAK E-commerce telah menjadi bagian integral dari sistem ekonomi global, memfasilitasi transaksi perdagangan secara digital. Namun, di dalam konteks ekonomi syariah, terdapat prinsip-prinsip yang harus diikuti untuk memastikan transaksi dilakukan sesuai dengan hukum Islam. Artikel ini bertujuan untuk mengkaji integrasi e-commerce dengan sistem ekonomi syariah, dengan mengidentifikasi tantangan, peluang, serta prinsip-prinsip ekonomi syariah yang relevan dalam praktik e-commerce. Penelitian ini menggunakan pendekatan kualitatif dengan studi literatur terkait e-commerce dan ekonomi syariah. Hasil penelitian menunjukkan bahwa meskipun terdapat tantangan dalam penerapan prinsip syariah pada platform digital, terdapat potensi besar bagi e-commerce syariah untuk berkembang dengan mengedepankan prinsip keadilan, transparansi, dan larangan riba.